FINANCIAL SPENDING RIGHTS OF THE TRUSTEE IN ISLAMIC FOUNDATIONS (AWQAF) LAW - Gürbüz, Mehmet; Erdem, Mehmet (Fırat University, 2022)
One of the most important issues in Islamic foundations law regarding foundation operations is the trustee and their dispositions. The present study discusses the financial dispositions of the trustee as the administrator of the foundation. Its purpose is to determine their dispositions that are/are not subject to compensation. Jurisprudential commandments regarding the financial management of trusts were detected based on works in the type of fiqh and fatwa.The trustee holds the position of guardian with respect to the ownership of the foundation, deputy with respect to the foundation or its beneficiaries, and entrusted and depository with respect to the income of the foundation. The fact that being a trustee does not involve ownership and compensation necessitates that the related dispositions are not primarily subjected to compensation. Since foundation assets are considered orphans' property, attention is paid to designate a trustworthy, pious, and dependable trustee. The trustee's dispositionsare governed by the conditions of the foundation, the Shari'a, and the judicial measure. The records state that these dispositions do not require compensationas long as they are not purposefully erroneous or involuntary and comply with the standards of committal. Compensation is due for dispositions of the trustee, such as noncompliance with the principles of committal, infringement of the conditions of the trust, excessive expenditures, and expenses on the foundation's decoration. It was observed that cases such as sale and trade processes harming the ownership of the trust as well as neglecting the mission of the trustresulted in dismissal from trusteeship. Issues such as dispositions towards the ownership of the trust, dismissal from entailment, long-term lease contracts and trade are generally under the authority of Islamic judges. It is stated with the rule “Trusteeship is stronger than state authority” that the trustee has priority compared to the judge in terms of dispositional authority on foundation properties.

İslâm vakıf hukukunda vakıf işlemleriyle ilgili en önemli problemlerden biri mütevellî ve onun tasarruflarıdır. Bu araştırmanın konusu vakfı yöneten kişi olarak mütevellînin mali tasarruflarıdır. Amacı ise onun tazmine konu olan ve olmayan tasarruflarını tespit etmektir. Vakfın mali yönetimine dair fıkhî hükümler fıkıh ve fetva türü eserlerden hareket edilerek tespit edilmiştir. Mütevellî; vakfın rakabesine nispetle vasî, vâkıfa ya da vakfın lehtarlarına nispetle vekil, vakfın gallesine nispetle ise mûdî’ (emanet bırakılan) ve yed-i emîn konumundadır. Mütevellî olmanın mülkiyet ve tazmini içermemesi, ilgili tasarrufların öncelikle tazmine konu olmamasını gerektirmektedir. Vakıf malları yetim malı mesabesinde görüldüğünden mütevellînin tayininde emin, takva ve istikamet sahibi kişilerden olmasına özen gösterilmiştir. Mütevellinin tasarrufları vâkıfın şartlarına, şer’î ilkelere ve kadr-ı ma’ruf ölçüsüne uygun olarak şekillenmektedir. Bu tasarrufların kasıt, kusur ve te’addî olmadığı ve emanet ilkelerine uygun olduğu sürece tazminle sonuçlanmadığı kayıtlarda yer almaktadır. Mütevellinin emanet ilkelerine uymayan; vakfiye şartlarına riayetsizlik, vakfın süslemesine yapılan harcamalar ve zaruri miktarı aşmak gibi tasarrufları tazminle sonuçlanmaktadır. Vakfın rakabesine zarar veren satım, istibdal, vakfın imaretinin ihmal edilmesi gibi durumların ise mütevellilikten’azl ile sonuçlandığı görülmüştür. Vakfın rakabesine yönelik tasarruflar, tevliyetten ’azil, icâre-i tavîle ve istibdâl ile ilgili hususlar ise genel olarak İslâm hâkiminin yetkisi dâhilinde olan konulardır. Mütevellinin vakıf mallarında tasarruf yetkisi hâkime göre öncelikli olduğu “Velâyet-i hâssa, velâyet-i ’âmmeden akvâdır.” kuralıyla ifade edilmektedir.
İslâm Vakıflar Hukukunda Mütevellî’nin Mali Tasarrufları
Keywords: Religious Studies; Din Araştırmaları